Healthy Child Uganda survey of knowledge, attitude and behaviour of village health team members toward their health care responsibilities in southwest Uganda - Scholastic, Ashaba; Kyomuhangi, Teddy; Santorino, Data; MacDonald, Noni; LeBlanc, John (Paediatrics & Child Health, 2012)
Developing countries have 25% of the global disease burden but only 1.3% of the health care professionals. While donor research focuses on important diagnostic and treatment advances, efforts to build local community-focused research capacity have been limited. Training and support for community based research is needed to address, with evidence, context-specific local problems that can lead to improved health outcomes – a must if Africa is to achieve the Millennium Goals of decreasing maternal mortality rates as well as those of children under five years of age. East Africa has bright young university health faculty who know the local health problems and understand the context but lack research skills and resources to address them. The Canadian Paediatric Society is concerned about child health globally. MicroResearch (MR), sponsored in part by the Canadian Paediatric Society, provides capacity building in community-based research through training, small grants and coaching from Canadian research experts who support eager interdisciplinary MR teams, at five sites in East Africa, with their local maternal/child health questions. All projects are aimed at improving health outcomes. The present MR brief report summarizes the findings from one MR project that determined the knowledge, attitudes and behaviors of village health team members toward their village health care responsibilities.
Keywords: Healthy Child Uganda; Village health team members; Uganda